Cloning, purification, crystallization and preliminary X‐ray studies of the putative transcriptional regulator SPD0280 from Streptococcus pneumoniae D39. Issue 11 (1st November 2013) - Zhang, Shaocheng; Min, Xun; Guo, Zhen; Zhang, Hongpeng; Huang, Ailong; Yin, Yibing; Wang, Deqiang
Abstract : Streptococcus pneumoniae SPD0280 is a hypothetical protein that has been putatively identified as a transcriptional regulator. However, it has very low sequence identity to other well characterized transcriptional regulators. Determination of the three‐dimensional structure may provide information for the characterization of proteins; therefore, it was decided to use X‐ray diffraction analysis to learn more about this protein. Here, the expression, purification, crystallization and preliminary crystallographic analysis of SPD0280 from S. pneumoniae are reported. The crystals belonged to space group P 21 21 21, with unit‐cell parameters a = 45.886, b = 66.785, c  = 150.050 Å, and diffracted to a resolution of 2.5 Å. The crystals are likely to contain one molecule in the asymmetric unit, with a V M value of 2.06 Å 3  Da −1 .